(3GdeNJUQ GdfGaYs - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s ((3eMeO Hf eMeO TajYs)
(3ChdgG (B:s
(3ChdgG(B: (3hEdG aef GdNdGa hEdG aeg ZjQg ef GdTLQ GdQWH hjcQg Hd GdNehQ HGdQjb hCf jYed deG jJHQC efg GdCcaGf GdMeGes
(3BNQgG (B:s
(3BNQgG(B: (3GdKGdKI dG jYbd GdYGbdI HgjeI hdG EJdGa eGd hjNJU VeGfgG HGdNjGfI Ydi ef MSHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 123s
(3GdPQjYI, L (B20: 141s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis